Attitude towards academic survey among audit firms in Malaysia: some challenges - Puat Nelson, Sherliza; Ahmad, Maslina; Zainal Abidin, Nor Hafizah (2018)
The objective of this research is to identify the possible responses among small and medium audit firms in Malaysia toward surveys. A total of 119 audit firms were involved in this survey. The list of firms was acquired from Malaysian Institute of Accountants (MIA), and the final sample consisted of firms particularly from Kuala Lumpur and Selangor. Questionnaire surveys were initially mailed to these firms, and several follow-ups were made for completed survey hence response rate was 16.4 percent. Follow-ups involved phone calls and visits to the firms. It is found that Malaysian audit firms are not very friendly and supportive to academic research.